Post-action determinants of the reported time of conscious intentions - Rigoni, Davide; Brass, Marcel; Sartori, Giuseppe (Frontiers in Human Neuroscience, 2010)
The question of whether our behaviour is guided by our conscious intentions is gaining momentum within the field of cognitive neuroscience. It has been demonstrated that the subjective experience that conscious intentions are the driving force of our actions, is built partially on a post hoc reconstruction. Our hypothesis was that this reconstructive process is mediated by an action-monitoring system that compares the predicted and the actual sensory consequences of an action. We applied Event Related Potentials (ERP) to a variant of the Libet’s task in which participants were asked to press a button and to report the time of decision –will judgment (W) – to press. We provided delayed auditory feedbacks after participants’ action to signify an action time later than the actual action. We found that auditory feedbacks evoked a negative component in the 250–300 time range, namely action-effect negativity (NAE), that is thought to reflect the activity of a system that detects violation from expectancies. We showed that the amplitude of the NAE was sensitive to the delay of the auditory feedback, with a larger amplitude for more delayed feedbacks. Furthermore, changes in the NAE were also associated with changes in the reported W. These results not only confirm that we infer the time we decided to act from events occurring after the response, but these results also indicate that the subjective experience of when an action is decided is influenced by the activity of an action-monitoring system that detects mismatches between predicted and actual sensory consequences of the actions.